ANALISIS IMPLEMENTASI UU PERLINDUNGAN ANAK TERHADAP PRAKTIK EKSPLOITASI EKONOMI ANAK OLEH ORANG TUA - Juhriati; Sahrul; Heru Setiawan (Sarau Institute, 2026)
Economic exploitation of minors, particularly by parents, is a complex phenomenon because it occurs within the private sphere of the family and is legitimized by social norms and economic pressures. This research is motivated by the increasing number of cases of children engaged in inappropriate work in the name of contributing to the family, without protection of their basic rights. The main objective of this study is to analyze the legal provisions in Law Number 35 of 2014 that regulate the prohibition and sanctions against child exploitation practices, and to evaluate the effectiveness of its implementation in cases of exploitation by parents. This study uses a normative legal research method with a statutory, conceptual, and case-based approach. Data were collected through a literature review of laws and regulations, court decisions, and relevant legal literature. The results indicate that although normatively, Law Number 35 of 2014, Law No. 35 of 2014 provides strong protection, but in practice, law enforcement against exploitative parents remains weak. Cultural factors, limited technical regulations, and resistance from law enforcement officials to intervening in family relationships are key obstacles.